Membrane trafficking and positioning of mGluRs at presynaptic and postsynaptic sites of excitatory synapses. (1st December 2021) - Bodzęta, Anna; Scheefhals, Nicky; MacGillavry, Harold D.
Abstract: The plethora of functions of glutamate in the brain are mediated by the complementary actions of ionotropic and metabotropic glutamate receptors (mGluRs). The ionotropic glutamate receptors carry most of the fast excitatory transmission, while mGluRs modulate transmission on longer timescales by triggering multiple intracellular signaling pathways. As such, mGluRs mediate critical aspects of synaptic transmission and plasticity. Interestingly, at synapses, mGluRs operate at both sides of the cleft, and thus bidirectionally exert the effects of glutamate. At postsynaptic sites, group I mGluRs act to modulate excitability and plasticity. At presynaptic sites, group II and III mGluRs act as auto-receptors, modulating release properties in an activity-dependent manner. Thus, synaptic mGluRs are essential signal integrators that functionally couple presynaptic and postsynaptic mechanisms of transmission and plasticity. Understanding how these receptors reach the membrane and are positioned relative to the presynaptic glutamate release site are therefore important aspects of synapse biology. In this review, we will discuss the currently known mechanisms underlying the trafficking and positioning of mGluRs at and around synapses, and how these mechanisms contribute to synaptic functioning. We will highlight outstanding questions and present an outlook on how recent technological developments will move this exciting research field forward. This article is part of the Neuropharmacology Special Issue on 'Glutamate Receptors – mGluRs'. Graphical abstract: Image 1 HIGHLIGHTS: The mGluR family comprises a functionally diverse group of receptors that are positioned at distinct subcellular sites Differential mechanisms regulate the formation, trafficking and positioning of mGluR subtypes The precise positioning of mGluRs determines their contribution to synaptic transmission and plasticity